Acorns (Quercus rotundifolia Lam.) and grass as natural sources of antioxidants and fatty acids in the “montanera” feeding of Iberian pig: Intra- and inter-annual variations - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Vázquez, F. M.; Cava, R. (Food Chemistry, 2011)
In two consecutive years (2006/2007 and 2007/2008), fortnightly samples were taken to characterise the antioxidant composition and fatty acid proﬁle of acorns and grass on which Iberian pigs feed during the period of ‘‘montanera” (free-range rearing system of the south-western of Iberian Peninsula). The antioxidant parameters analysed were: a- and c-tocopherol, total phenolics compounds (TPC), lipophilic and hydrophilic antioxidant activities (LAA, HAA) (acorn and grass) and condensed and hydrolysable tannins (CT, HT) and protein precipitating capacity (PP) (acorns). To characterise the fatty acid proﬁles, the thirteen major fatty acids were assayed. For the acorns, it was found that there was intra-annual variability in all the antioxidants studied except a-tocopherol, and inter-annual variability in all except the protein precipitating capacity. The fatty acid proﬁle also varied depending on the sampling date and the study year, especially in the saturated fatty acids (SFA) and C18:1 n-9 content. For the grass, there was intraand inter-annual variability in all the antioxidant parameters studied, and in the proportions of the fatty acids C18:0, and C18:1. It could explain variations in the antioxidant and fatty acids composition of Iberian pig tissues from animals raised in different ‘‘montanera” seasons and even in the same ‘‘montanera” season.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorn; antioxidant; fatty acid; Grass; iberian pig; ‘‘Montanera”

Interannual variability and evolution during the montanera period of Holm oak (Quercus rotundifolia Lam.) acorns - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Cava, R.; Vázquez, F. M. (Spanish Journal of Agricultural Research, 2010)
Eighty-eight samples of Quercus rotundifolia acorns were analyzed during three consecutive years (2005/06, 2006/07 and 2007/08) to determine variations in their morphology, sanitary condition, and nutritional composition throughout the same period of montanera (free-range swine-raising system of SW Iberia) and between different years of study. Results showed that morphological characteristics remained constant throughout montanera season. Fungal damage increased, and Curculio sp. and Cydia sp. pests decreased over the course of the montanera season. Dry matter content decreased in both kernel and pericarp (P < 0.001), while the crude fiber and protein contents were not modified. The ash, nitrogen-free extract, and fat contents, however, were also affected by sampling date within a montanera season. With respect to the interannual variability, variations (P < 0.05) were observed in all the variables studied. It is therefore confirmed that there is variability in the sanitary condition and nutritional composition of acorns within the same montanera season and between different years of study. These could explain the differences in the chemical characteristics of Iberian pig tissues from animals raised in different montanera seasons, and even during the same montanera season.
Keywords: acorn sanitary condition; Dehesa; feeding; Iberian pigs; proximate composition